The Many Faces of Hegemony: Social Complexity and Political Strategies - Vincenzo Maria Di Mino ([sic])
In recent decades, the concept of “complexity” has been one of the leitmotifs of social science used to open the conceptual baggage needed to understand the dynamics of “post-modernity,” primarily the composition and structure of society, and the mutations of the technologies of government. Alex Williams, a British political scientist, is best known for the important work Inventing the Future: Postcapitalism and a World Without Work, co-written with Nick Srnicek, which posed the politically dense and central problem of the collective use of technologies to “accelerate” the overcoming of capitalism. His latest book, Political Hegemony and Social Complexity: Mechanism of Power After Gramsci, elaborates on some of the diagnoses set out in the previous one, especially those concerning neoliberalism as not merely an economic but a total social phenomenon, and those on the ambivalent, porous, and productive intertwining of politics and technology. The focus on hegemony allows Williams to connect the cultural utopia of accelerationism to antagonistic political practice by comparing the previously elaborated concept of “folk politics” with the theme of organization. Among the many lines of interpretation that the political machine of hegemony possesses, one certainly refers to the renewal of left politics, that is, to the overcoming of the stasis between Party and Movement, between Ideology and Culture, between State and Opposition.